Intergenerational transitions in age at menarche: insights from Chandauli district, Uttar Pradesh, India - Sumedha; Suman Singh; Praveen Kumar Pathak (BMC Women's Health)
Abstract Background Menarche, a milestone in a woman’s reproductive journey, is influenced by various factors such as lifestyle and dietary habits. Recent studies have corroborated this claim and prompted further investigation. This study explores the connection between menarche timing with lifestyle and dietary habits among three generations of women from the Sakaldiha block of Chandauli district and presents valuable insights into the role of diet and lifestyle in this crucial reproductive event. Methods The study is based on primary data collected using multistage stratified random sampling. A comparative analysis of the mean age at menarche across independent variables has been conducted using the one-way analysis of variance (ANOVA) technique. Additionally, a multiple regression model has been developed to investigate the association between menarcheal age and various dietary, lifestyle and socio-economic factors among 400 respondents. Results The average age of menarche for respondents was 14.29 years (95% CI: 14.12, 14.45), which has decreased by 1.66 years from 14.89 years (95% CI: 14.63, 15.15) in women over 40 years of age to 13.23 years (95% CI: 12.97, 13.49) in the < 20 years age group. The study additionally found that dietary and lifestyle factors had an impact on the age of menarche, with those who regularly consumed junk food, occasionally ate meat/fish or eggs, completely avoided curd or buttermilk and engaged in non-resting leisure activities experiencing an earlier onset of menarche. Conclusion The study shows that diet and lifestyle affect age at menarche, with current generations experiencing an earlier onset of menstruation. The effect of socioeconomic status remains inconclusive.